Decoding the therapeutic mechanism of Conocarpus lancifolius in hepatocellular carcinoma: network pharmacology, molecular docking, and LC-MS QTOF insights - Prajapati, Poojaben M.; Patel, Saumya K.; Rawal, Rakesh M.; Lakhani, Komal G.; Hamid, Rasmieh; Maitreya, Bharat B. (Frontiers in Pharmacology, 2025)
Hepatocellular carcinoma is a multifaceted and lethal malignancy, ranking third in cancer-related mortality and sixth in worldwide incidence. This study aimed to utilize LCMS-QTOF analysis to identify the phytoconstituents of C. lancifolius across three distinct seasons. The study also sought to elucidate the multi-layered mechanism of action against hepatocellular carcinoma using network pharmacology analysis, molecular docking, and molecular dynamics simulation. A total of 352 phytoconstituents were identified in the extract of Conocarpus lancifolius, of which 154 compounds were chosen for subsequent in silico analysis. Network construction and Gene Ontology (GO) enrichment analysis were performed using ShinyGo and the KEGG database, while Cytoscape 3.10.2 was employed for network visualization and analysis. Molecular docking analyses were conducted using YASARA software, and the highest-scoring compounds and targets underwent 100 ns molecular dynamics simulations via Schrödinger Desmond. CytoHubba identified ten key hub genes, including CASP3, STAT3, and EGFR. GO and KEGG analyses revealed significant biological processes, molecular functions, cellular components, and pathways, including PPAR signaling, thyroid cancer, and prolactin pathways. Notably, phytochemicals from C. lancifolius, particularly Alnusiin, Egrosine, and Yessotoxin, exhibited strong binding affinities with CASP3 and STAT3. The structural stability of Alnusiin in complex with these target proteins was confirmed through molecular dynamics simulation, indicating its potential as a promising anti-HCC agent. This study integrates network pharmacology, molecular docking, and molecular dynamics simulations to characterize the bioactive compounds in C. lancifolius and elucidate a plausible mechanism for its therapeutic action against hepatocellular carcinoma.